Spatial Analysis of Several Technical Criteria for Industrial Area Feasibility (Ki) - Sarif Robo; Kusman Malik; Nurul Ainun Tangge; Krishna Aji; Gunawan Hartono (Journal of Synergy Landscape, 2023)
Industrial Estates in general must see the feasibility of various basic aspects of the Region, especially the land aspect. Non-financial aspects of industrial estates in terms of markets and marketing currently have many competitors. This study aims to map the technical criteria for the feasibility of spatial-based district industrial estates and recommendations for the feasibility of developing industrial estates and industrial areas in the Sula Islands Regency of North Maluku Province. This research uses a descriptive qualitative method. Data analysis consists of analyzing the basic physical aspects of the area, which consists of analyzing slope, shape of the area, soil type geological formation, land elevation and land use. Analysis of the basic physical aspects of the area of technical criteria for the feasibility of industrial areas is carried out by overlaying map layer techniques so as to produce a map of industrial feasible areas or a map of district industrial designations. The results of the analysis show that the development of industrial areas in the Sula Islands Regency of North Maluku Province is very feasible for small and medium industries and large industries in accordance with the existing area and the potential of the area. Industrial estates are recommended in areas with slope levels (≤ 15%) and are located in other use areas spread across sub-districts.